Updated distribution mapping of Posidonia oceanica meadows, coralligenous assemblages and marine caves in the Mediterranean Sea: implications for conservation and restoration - VASILIS GEROVASILEIOU; ANTONIO SÁNCHEZ-ESPINOSA; DAVID RODRÍGUEZ-RODRÍGUEZ; SIMONETTA FRASCHETTI; INÉS MAZARRASA; CYRINE BOUAFIF; ATEF OUERGHI; DANIA ABDUL MALAK (Mediterranean Marine Science, 2026)
Marine habitats in the Mediterranean Sea play a vital role in supporting biodiversity, ecosystem functioning and services, and climate resilience. However, they are facing escalating threats from anthropogenic pressures. This study, coordinated and financially supported by the Specially Protected Areas Regional Activity Centre (SPA/RAC) under the Barcelona Convention, presents an updated, harmonized assessment of the distribution and protection status of three iconic benthic habitats: Posidonia oceanica meadows, coralligenous assemblages, and marine caves. A standardized methodology was applied to compile, review, harmonize, and aggregate fine-scale data from regional databases, National Focal Points (NFPs), expert networks, and online repositories. Posidonia oceanica meadows were mapped over 22,379 km² across 15 Mediterranean countries, with 95% within territorial waters and 37% in Marine Protected Areas (MPAs). Coralligenous assemblages and maërl beds covered 2,889.5 km² in 13 countries, in line with previous modelling estimates, with 67.1% located within MPAs, particularly in the central and western regions. Approximately 3,000 marine caves were identified across 15 countries, representing the first country-level spatial inventory of this habitat. Nearly 69% of known caves are located in MPAs, although lacking specific conservation measures. Despite significant progress, notable limitations remain. Data quality and availability are uneven across regions, and inconsistencies in classification, spatial resolution, and ecological descriptors – especially for coralligenous assemblages and marine cave typologies – limit detailed habitat representation. This study highlights persistent knowledge gaps in parts of North Africa, the Eastern Mediterranean, and non-EU coastal states, and provides a robust baseline for conservation planning and supports regional monitoring efforts under the Barcelona Convention. Future priorities include addressing data gaps, standardizing classification systems, prioritizing sites for conservation and restoration to strengthen marine habitat protection and recovery and enhance the ecological effectiveness of MPAs.